USING ENGLISH SONGS TO INCREASE EARLY STUDENTSâ VOCABULARY - Fachraini, Siti (Getsempena English Education Journal, 2017)
Early childhood is a child in the age of 0-6 years. In this age, the development and growth of physical and mental of children develop rapidly. Meanwhile, the aspects developed in early childhood education are: religious and moral values, physical (consisting of gross motor, fine motor and physical health), cognitive (consisting of general knowledge and science, concepts, shapes, colors, sizes and patterns, number concepts, symbols of numbers and letters), language (consisting of accepting language, expressing language and script) and emotional social. Language skills are one of the aspects which are developed at this age. Therefore, researchers intend to examine the level of mastery of the language of children through the song. This study aims to improve the vocabulary of early childhood, where this result affects the childrenâs ability to speak a foreign language in the future. This study is a Classroom Action Research, which aims to improve the ability of children English by using songs on the student group B TK Takrimah Tungkob Aceh Besar. This classroom action research is conducted in three cycles; each cycle consists of four stages: planning, action, observation, and reflection. Moreover, in analyzing the data, the researcher used descriptive method, that is analyzed data implemented since learning and developed during the process of reflection until process of report preparation. Data collection techniques used in this study include: interview, and observation of teaching and learning activities. Data analysis techniques consisted of three activities, namely data reduction, data presentation and conclusion drawing. The results showed that 64% of students can mentioned correctly alphabet in English in the first cycle. Furthermore, 80% of students have known and can properly name a few nouns in English in the second cycle. Furthermore, in the third cycle, 88% of students have been able to use the noun in the form of a simple sentence. Based on the results of this study, it is very important for Kindergarten teachers to create an atmosphere of learning that makes students motivated and eager in learning such as the use of video media in learning so that automatically can improve students abilities and achievement.Â Keywords: Early Childhood, English Vocabulary